Pseudo-Random Signal Injection for Position Sensorless Control of Five-Phase IPMSM Based on Third Harmonic Space - Yuhao Zhang; Chen Chen; Zhengmeng Liu; Qian Chen; Jiahao Zhang; Guohai Liu (IEEE Access, 2023)
In this article, a position sensorless control strategy for the five-phase interior permanent magnet synchronous motor (IPMSM) by injecting pseudo-random signal into the third harmonic space is proposed. The conventional sensorless control of five-phase IPMSM based on third harmonic space extracts rotor position signal by injecting high-frequency square voltage signals into the third harmonic space. However, high-frequency square-wave voltage injection (HFSVI) produces a loud audible noise. Different from the conventional HFSVI strategy, the proposed strategy injects simplified pseudo-random fixed-frequency phase-switching (SPRFFPS) signal into the third harmonic space of the five-phase IPMSM to reduce high-frequency audible noise. To verify the effectiveness of the proposed strategy, the power spectral density (PSD) of phase current is analyzed. Also, since high-frequency signal is not injected into the fundamental space, the digital filter in the fundamental space current loop will no longer be needed, which avoids time delay and degradation of control performance. Finally, the correctness of the proposed strategy is verified by experiments.